If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2 + w) = -20 (2 * -2 + w * -2) = -20 (-4 + -2w) = -20 Solving -4 + -2w = -20 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -2w = -20 + 4 Combine like terms: -4 + 4 = 0 0 + -2w = -20 + 4 -2w = -20 + 4 Combine like terms: -20 + 4 = -16 -2w = -16 Divide each side by '-2'. w = 8 Simplifying w = 8
| -15=6g-3 | | 50x+3=7 | | 42=6x+7 | | x/3-2=5 | | 4(q-5)=16 | | 8a+10b=6 | | 2Y^2+9Y-5= | | 4y=208-6x | | x^3-6x^2+16X=96 | | 2(3x-4)=28 | | 0.5x-1.5=2.5 | | 5.4+-3(4m+3)=45.7 | | 6x+14x=16 | | 2(3x+7)-(x-4)= | | -6y+15=-9 | | -6+3y/5=3 | | -2(5)+2=5y-1 | | 3(4y-7)=6 | | 8(x+3)=10(x+7) | | (-2)(-7)=14 | | 9(5x-2)=17 | | 2a/5+5=1 | | (6x+2)+(4x+8)= | | k/5-6=2 | | 2-3c=-7 | | 8x=10-11x | | 2n/3+5=7 | | 7x+2=20+3x+8 | | 12-x=16 | | -7-x=5 | | 2(n-5)=4-2(7-n) | | 2(x+2)=34 |